Cattle grazing controls non-native grass invasion and restores ground layer diversity and structure in tropical open ecosystems - Bruna H. Campos; Jennifer L. Funk; Natashi Pilon; Andra C. Dalbeto; Giselda Durigan (Agriculture, Ecosystems & Environment, 2026)

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Population Genomics Reveals Local Adaptation Related to Temperature Variation in Two Stream Frog Species: Implications for Vulnerability to Climate Warming - Brenna R. Forester; Amanda S. Cicchino; Alisha A. Shah; Austin B. Mudd; Eric C. Anderson; Jessen V. Bredeson; Andrew J. Crawford; Jason B. Dunham; Cameron K. Ghalambor; Erin L. Landguth; Brent W. Murray; Daniel Rokhsar; et al. (Molecular Ecology, 2025)
Identifying populations at highest risk from climate change is a critical component of conservation efforts. However, vulnerability assessments are usually applied at the species level, even though intraspecific variation in exposure, sensitivity and adaptive capacity play a crucial role in determining vulnerability. Genomic data can inform intraspecific vulnerability by identifying signatures of local adaptation that reflect population‐level variation in sensitivity and adaptive capacity. Here, we address the question of local adaptation to temperature and the genetic basis of thermal tolerance in two stream frogs ( Ascaphus truei and A. montanus ). Building on previous physiological and temperature data, we used whole‐genome resequencing of tadpoles from four sites spanning temperature gradients in each species to test for signatures of local adaptation. To support these analyses, we developed the first annotated reference genome for A. truei . We then expanded the geographic scope of our analysis using targeted capture at an additional 11 sites per species. We found evidence of local adaptation to temperature based on physiological and genomic data in A. montanus and genomic data in A. truei , suggesting similar levels of sensitivity (i.e., susceptibility) among populations regardless of stream temperature. However, invariant thermal tolerances across temperatures in A. truei suggest that populations occupying warmer streams may be most sensitive. We identified high levels of evolutionary potential in both species based on genomic and physiological data. While further integration of these data is needed to comprehensively evaluate spatial variation in vulnerability, this work illustrates the value of genomics in identifying spatial patterns of climate change vulnerability.

P18-72 Integration of Metabolomics and Transcriptomics, as well as Mitostress, CALUX Assays and Targeted Proteomics for an Improved Mechanism-based Hazard Characterization of Drug-induced Liver Injury - F. Zickgraf; L. Wijaya; T. de Boer; C. Budin; S. Moco; V. Pozo Garcia; O. Pötz; P. Ternes; V. Giri; B. van de Water; C. Gomes; H. Kamp; et al. (Toxicology Letters, 2025)

P18-103 Historical control database and acceptance criteria for a comparative in vitro hepatic enzyme assay(KaLy-Cell method) - S. Kellum; K. Choudhury; S. Melching-Kollmuss; A. Schafer; C. Parmentier; X. Sopko; L. Richert; H. Tinwell; C. Walter; I. Wohlman; F. Zhang; S. Catalano; et al. (Toxicology Letters, 2025)

Lungen-Organoide bringen neuen Schwung in die COPD-Forschung - Lili Rusznyak; Roxana-Maria Wasnick; Maja C. Funk (BIOspektrum, 2025)
Chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide and a systemic chronic inflammatory disease. It is caused by factors such as aging and environmental pollution, and characterized by a dysfunction of the epithelium and immune defense. Lung organoids allow us to investigate how aging and environmental stressors impair epithelial regeneration and promote inflammation. These models enable the discovery of novel mechanisms and therapies for COPD and its associated comorbidities.

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

P13-29 A new mutagenicity NAM: An in vitro Transgenic Rodent (TGR) assay for the detection of mutagens and assessment of their mechanism of action - D. Funk-Weyer; R. Landsiedel; A. Göpfert; C. Rülker; M. Eichenlaub; B. Tokovenko; N. Honarvar; D. Schuster (Toxicology Letters, 2024)

P09-12 Thyroid hormones concentrations in cerebellum, cortex and whole-brain rat samples at certain life stages - C. Hindrichs; T. Walk; S. Melching-Kollmuss; R. Landsiedel; S. Schneider; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2024)

P06-23 Integration of metabolomics and transcriptomics for improved mechanism-based hazard characterization of drug-induced liver injury - F.M. Zickgraf; L. Wijaya; T. de Boer; C. Budin; S. Moco; V. Pozo Garcia; P. Ternes; V. Giri; C. Gomes; B. van de Water; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2024)

Sailing the Seven Seas: A Multinational Comparison of ChatGPT’s Performance on Medical Licensing Examinations - Michael Alfertshofer; Cosima C. Hoch; Paul F. Funk; Katharina Hollmann; Barbara Wollenberg; Samuel Knoedler; Leonard Knoedler (Annals of Biomedical Engineering, 2024)
Purpose The use of AI-powered technology, particularly OpenAI’s ChatGPT, holds significant potential to reshape healthcare and medical education. Despite existing studies on the performance of ChatGPT in medical licensing examinations across different nations, a comprehensive, multinational analysis using rigorous methodology is currently lacking. Our study sought to address this gap by evaluating the performance of ChatGPT on six different national medical licensing exams and investigating the relationship between test question length and ChatGPT’s accuracy. Methods We manually inputted a total of 1,800 test questions (300 each from US, Italian, French, Spanish, UK, and Indian medical licensing examination) into ChatGPT, and recorded the accuracy of its responses. Results We found significant variance in ChatGPT’s test accuracy across different countries, with the highest accuracy seen in the Italian examination (73% correct answers) and the lowest in the French examination (22% correct answers). Interestingly, question length correlated with ChatGPT’s performance in the Italian and French state examinations only. In addition, the study revealed that questions requiring multiple correct answers, as seen in the French examination, posed a greater challenge to ChatGPT. Conclusion Our findings underscore the need for future research to further delineate ChatGPT’s strengths and limitations in medical test-taking across additional countries and to develop guidelines to prevent AI-assisted cheating in medical examinations.

Venlafaxine’s therapeutic reference range in the treatment of depression revised: a systematic review and meta-analysis - X.M. Lense; C. Hiemke; C.S.M. Funk; U. Havemann-Reinecke; G. Hefner; A. Menke; R. Mössner; T.G. Riemer; M. Scherf-Clavel; G. Schoretsanitis; G. Gründer; X.M. Hart (Psychopharmacology, 2024)
Introduction The selective serotonin and norepinephrine reuptake inhibitor venlafaxine is among the most prescribed antidepressant drugs worldwide and, according to guidelines, its dose titration should be guided by drug-level monitoring of its active moiety (AM) which consists of venlafaxine (VEN) plus active metabolite O-desmethylvenlafaxine (ODV). This indication of therapeutic drug monitoring (TDM), however, assumes a clear concentration/effect relationship for a drug, which for VEN has not been systematically explored yet. Objectives We performed a systematic review and meta-analysis to investigate the relationship between blood levels, efficacy, and adverse reactions in order to suggest an optimal target concentration range for VEN oral formulations for the treatment of depression. Methods Four databases (MEDLINE (PubMed), PsycINFO, Web of Science Core Collection, and Cochrane Library) were systematically searched in March 2022 for relevant articles according to a previously published protocol. Reviewers independently screened references and performed data extraction and critical appraisal. Results High-quality randomized controlled trials investigating concentration/efficacy relationships and studies using a placebo lead-in phase were not found. Sixty-eight articles, consisting mostly of naturalistic TDM studies or small noncontrolled studies, met the eligibility criteria. Of them, five cohort studies reported a positive correlation between blood levels and antidepressant effects after VEN treatment. Our meta-analyses showed (i) higher AM and (ii) higher ODV concentrations in patients responding to VEN treatment when compared to non-responders ( n = 360, k = 5). AM concentration-dependent occurrence of tremor was reported in one study. We found a linear relationship between daily dose and AM concentration within guideline recommended doses (75–225 mg/day). The population-based concentration ranges (25–75% interquartile) among 11 studies ( n = 3200) using flexible dosing were (i) 225–450 ng/ml for the AM and (ii) 144–302 ng/ml for ODV. One PET study reported an occupancy of 80% serotonin transporters for ODV serum levels above 85 ng/ml. Based on our findings, we propose a therapeutic reference range for AM of 140–600 ng/ml. Conclusion VEN TDM within a range of 140 to 600 ng/ml (AM) will increase the probability of response in nonresponders. A titration within the proposed reference range is recommended in case of non-response at lower drug concentrations as a consequence of VEN’s dual mechanism of action via combined serotonin and norepinephrine reuptake inhibition. Drug titration towards higher concentrations will, however, increase the risk for ADRs, in particular with supratherapeutic drug concentrations.

Conservation genomics of an endangered montane amphibian reveals low population structure, low genomic diversity and selection pressure from disease - D. R. Trumbo; B. M. Hardy; H. J. Crockett; E. Muths; B. R. Forester; R. G. Cheek; S. J. Zimmerman; S. Corey‐Rivas; L. L. Bailey; W. C. Funk (Molecular Ecology, 2023)
Wildlife diseases are a major global threat to biodiversity. Boreal toads ( Anaxyrus [Bufo] boreas ) are a state‐endangered species in the southern Rocky Mountains of Colorado and New Mexico, and a species of concern in Wyoming, largely due to lethal skin infections caused by the amphibian chytrid fungus Batrachochytrium dendrobatidis ( Bd ). We performed conservation and landscape genomic analyses using single nucleotide polymorphisms from double‐digest, restriction site‐associated DNA sequencing in combination with the development of the first boreal toad (and first North American toad) reference genome to investigate population structure, genomic diversity, landscape connectivity and adaptive divergence. Genomic diversity ( π = 0.00034–0.00040) and effective population sizes ( N e = 8.9–38.4) were low, likely due to post‐Pleistocene founder effects and Bd ‐related population crashes over the last three decades. Population structure was also low, likely due to formerly high connectivity among a higher density of geographically proximate populations. Boreal toad gene flow was facilitated by low precipitation, cold minimum temperatures, less tree canopy, low heat load and less urbanization. We found >8X more putatively adaptive loci related to Bd intensity than to all other environmental factors combined, and evidence for genes under selection related to immune response, heart development and regulation and skin function. These data suggest boreal toads in habitats with Bd have experienced stronger selection pressure from disease than from other, broad‐scale environmental variations. These findings can be used by managers to conserve and recover the species through actions including reintroduction and supplementation of populations that have declined due to Bd .

P08-13: Analysis of Thyroid Hormone Metabolites in Rat Brain using an automated online-SPE-LC-MS/MS method - C. Hindrichs; T. Walk; S. Melching-Kollmuss; R. Landsiedel; H. Kamp; D. Funk-Weyer (Toxicology Letters, 2023)

Genetic diversity goals and targets have improved, but remain insufficient for clear implementation of the post-2020 global biodiversity framework - Sean Hoban; Michael W. Bruford; Jessica M. da Silva; W. Chris Funk; Richard Frankham; Michael J. Gill; Catherine E. Grueber; Myriam Heuertz; Margaret E. Hunter; Francine Kershaw; Robert C. Lacy; Caroline Lees; et al. (Conservation Genetics, 2023)
Genetic diversity among and within populations of all species is necessary for people and nature to survive and thrive in a changing world. Over the past three years, commitments for conserving genetic diversity have become more ambitious and specific under the Convention on Biological Diversity’s (CBD) draft post-2020 global biodiversity framework (GBF). This Perspective article comments on how goals and targets of the GBF have evolved, the improvements that are still needed, lessons learned from this process, and connections between goals and targets and the actions and reporting that will be needed to maintain, protect, manage and monitor genetic diversity. It is possible and necessary that the GBF strives to maintain genetic diversity within and among populations of all species, to restore genetic connectivity, and to develop national genetic conservation strategies, and to report on these using proposed, feasible indicators.

A metabolomic signature of the APOE2 allele - Paola Sebastiani; Zeyuan Song; Dylan Ellis; Qu Tian; Michaela Schwaiger-Haber; Ethan Stancliffe; Michael S. Lustgarten; Cory C. Funk; Priyanka Baloni; Cong-Hui Yao; Shakchhi Joshi; Megan M. Marron; et al. (GeroScience, 2023)

Reproductive benefits associated with dispersal in headwater populations of Trinidadian guppies ( Poecilia reticulata ) - Isabela L. Borges; Jillian C. Dangerfield; Lisa M. Angeloni; W. Chris Funk; Sarah W. Fitzpatrick (Ecology Letters, 2022)
Theory suggests that the evolution of dispersal is balanced by its fitness costs and benefits, yet empirical evidence is sparse due to the difficulties of measuring dispersal and fitness in natural populations. Here, we use spatially explicit data from a multi‐generational capture–mark–recapture study of two populations of Trinidadian guppies ( Poecilia reticulata ) along with pedigrees to test whether there are fitness benefits correlated with dispersal. Combining these ecological and molecular data sets allows us to directly measure the relationship between movement and reproduction. Individual dispersal was measured as the total distance moved by a fish during its lifetime. We analysed the effects of dispersal propensity and distance on a variety of reproductive metrics. We found that number of mates and number of offspring were positively correlated to dispersal, especially for males. Our results also reveal individual and environmental variation in dispersal, with sex, size, season, and stream acting as determining factors.

A unifying framework for analyzing temporal changes in functional and taxonomic diversity along disturbance gradients - Erin I. Larson; N. LeRoy Poff; W. Chris Funk; Rachel A. Harrington; Boris C. Kondratieff; Scott G. Morton; Alexander S. Flecker (Ecology, 2021)
Frameworks exclusively considering functional diversity are gaining popularity, as they complement and extend the information provided by taxonomic diversity metrics, particularly in response to disturbance. Taxonomic diversity should be included in functional diversity frameworks to uncover the functional mechanisms causing species loss following disturbance events. We present and test a predictive framework that considers temporal functional and taxonomic diversity responses along disturbance gradients. Our proposed framework allows us to test different multidimensional metrics of taxonomic diversity that can be directly compared to calculated multidimensional functional diversity metrics. It builds on existing functional diversity–disturbance frameworks both by using a gradient approach and by jointly considering taxonomic and functional diversity. We used previously unpublished stream insect community data collected prior to, and for the two years following, an extreme flood event that occurred in 2013. Using 14 northern Colorado mountain streams, we tested our framework and determined that taxonomic diversity metrics calculated using multidimensional methods resulted in concordance between taxonomic and functional diversity responses. By considering functional and taxonomic diversity together and using a gradient approach, we were able to identify some of the mechanisms driving species losses following this extreme disturbance event.

Temperature dependence of metabolic rate in tropical and temperate aquatic insects: Support for the Climate Variability Hypothesis in mayflies but not stoneflies - Alisha A. Shah; H. Arthur Woods; Justin C. Havird; Andrea C. Encalada; Alexander S. Flecker; W. Chris Funk; Juan M. Guayasamin; Boris C. Kondratieff; N. LeRoy Poff; Steven A. Thomas; Kelly R. Zamudio; Cameron K. Ghalambor (Global Change Biology, 2021)
A fundamental gap in climate change vulnerability research is an understanding of the relative thermal sensitivity of ectotherms. Aquatic insects are vital to stream ecosystem function and biodiversity but insufficiently studied with respect to their thermal physiology. With global temperatures rising at an unprecedented rate, it is imperative that we know how aquatic insects respond to increasing temperature and whether these responses vary among taxa, latitudes, and elevations. We evaluated the thermal sensitivity of standard metabolic rate in stream‐dwelling baetid mayflies and perlid stoneflies across a ~2,000 m elevation gradient in the temperate Rocky Mountains in Colorado, USA, and the tropical Andes in Napo, Ecuador. We used temperature‐controlled water baths and microrespirometry to estimate changes in oxygen consumption. Tropical mayflies generally exhibited greater thermal sensitivity in metabolism compared to temperate mayflies; tropical mayfly metabolic rates increased more rapidly with temperature and the insects more frequently exhibited behavioral signs of thermal stress. By contrast, temperate and tropical stoneflies did not clearly differ. Varied responses to temperature among baetid mayflies and perlid stoneflies may reflect differences in evolutionary history or ecological roles as herbivores and predators, respectively. Our results show that there is physiological variation across elevations and species and that low‐elevation tropical mayflies may be especially imperiled by climate warming. Given such variation among species, broad generalizations about the vulnerability of tropical ectotherms should be made more cautiously.

Why predict climate hazards if we need to understand impacts? Putting humans back into the drought equation - M. Enenkel; M. E. Brown; J. V. Vogt; J. L. McCarty; A. Reid Bell; D. Guha-Sapir; W. Dorigo; K. Vasilaky; M. Svoboda; R. Bonifacio; M. Anderson; C. Funk; et al. (Climatic Change, 2020)

Assessing North American multimodel ensemble (NMME) seasonal forecast skill to assist in the early warning of anomalous hydrometeorological events over East Africa - Shraddhanand Shukla; Jason Roberts; Andrew Hoell; Christopher C. Funk; Franklin Robertson; Ben Kirtman (Climate Dynamics, 2019)

Elucidating the symbiotic interactions between a locally isolated microalga Chlorella vulgaris and its co-occurring bacterium Rhizobium sp. in synthetic municipal wastewater - L. Ferro; M. Colombo; E. Posadas; C. Funk; R. Muñoz (Journal of Applied Phycology, 2019)

Improving conservation policy with genomics: a guide to integrating adaptive potential into U.S. Endangered Species Act decisions for conservation practitioners and geneticists - W. C. Funk; Brenna R. Forester; Sarah J. Converse; Catherine Darst; Steve Morey (Conservation Genetics, 2019)

An experimental test of alternative population augmentation scenarios - John A. Kronenberger; Jill C. Gerberich; Sarah W. Fitzpatrick; E. Dale Broder; Lisa M. Angeloni; W. Chris Funk (Conservation Biology, 2018)
Human land use is fragmenting habitats worldwide and inhibiting dispersal among previously connected populations of organisms, often leading to inbreeding depression and reduced evolutionary potential in the face of rapid environmental change. To combat this augmentation of isolated populations with immigrants is sometimes used to facilitate demographic and genetic rescue. Augmentation with immigrants that are genetically and adaptively similar to the target population effectively increases population fitness, but if immigrants are very genetically or adaptively divergent, augmentation can lead to outbreeding depression. Despite well‐cited guidelines for the best practice selection of immigrant sources, often only highly divergent populations remain, and experimental tests of these riskier augmentation scenarios are essentially nonexistent. We conducted a mesocosm experiment with Trinidadian guppies (Poecilia reticulata) to test the multigenerational demographic and genetic effects of augmenting 2 target populations with 3 types of divergent immigrants. We found no evidence of demographic rescue, but we did observe genetic rescue in one population. Divergent immigrant treatments tended to maintain greater genetic diversity, abundance, and hybrid fitness than controls that received immigrants from the source used to seed the mesocosms. In the second population, divergent immigrants had a slightly negative effect in one treatment, and the benefits of augmentation were less apparent overall, likely because this population started with higher genetic diversity and a lower reproductive rate that limited genetic admixture. Our results add to a growing consensus that gene flow can increase population fitness even when immigrants are more highly divergent and may help reduce uncertainty about the use of augmentation in conservation.

Extreme streams: species persistence and genomic change in montane insect populations across a flooding gradient - N. LeRoy Poff; Erin I. Larson; Patricia E. Salerno; Scott G. Morton; Boris C. Kondratieff; Alexander S. Flecker; Kelly R. Zamudio; W. Chris Funk (Ecology Letters, 2018)
The ecological and evolutionary consequences of extreme events are poorly understood. Here, we tested predictions about species persistence and population genomic change in aquatic insects in 14 Colorado mountain streams across a hydrological disturbance gradient caused by a one in 500‐year rainfall event. Taxa persistence ranged from 39 to 77% across sites and declined with increasing disturbance in relation to species' resistance and resilience traits. For taxa with mobile larvae and terrestrial adult stages present at the time of the flood, average persistence was 84% compared to 25% for immobile taxa that lacked terrestrial adults. For two of six species analysed, genomic diversity (allelic richness) declined after the event. For one species it greatly expanded, suggesting resilience via re‐colonisation from upstream populations. Thus, while resistance and resilience traits can explain species persistence to extreme disturbance, population genomic change varies among species, challenging generalisations about evolutionary responses to extreme events at landscape scales.

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

Locally adapted traits maintained in the face of high gene flow - S. W. Fitzpatrick; J. C. Gerberich; J. A. Kronenberger; L. M. Angeloni; W. C. Funk (Ecology Letters, 2015)
Gene flow between phenotypically divergent populations can disrupt local adaptation or, alternatively, may stimulate adaptive evolution by increasing genetic variation. We capitalised on historical Trinidadian guppy transplant experiments to test the phenotypic effects of increased gene flow caused by replicated introductions of adaptively divergent guppies, which were translocated from high‐ to low‐predation environments. We sampled two native populations prior to the onset of gene flow, six historic introduction sites, introduction sources and multiple downstream points in each basin. Extensive gene flow from introductions occurred in all streams, yet adaptive phenotypic divergence across a gradient in predation level was maintained. Descendants of guppies from a high‐predation source site showed high phenotypic similarity with native low‐predation guppies in as few as ~12 generations after gene flow, likely through a combination of adaptive evolution and phenotypic plasticity. Our results demonstrate that locally adapted phenotypes can be maintained despite extensive gene flow from divergent populations.

Water availability strongly impacts population genetic patterns of an imperiled Great Plains endemic fish - S. W. Fitzpatrick; H. Crockett; W. C. Funk (Conservation Genetics, 2014)

Developing seasonal rainfall scenarios for food security early warning - Gregory J. Husak; Christopher C. Funk; Joel Michaelsen; Tamuka Magadzire; Kirk P. Goldsberry (Theoretical and Applied Climatology, 2013)

Pollen morphology and its taxonomic significance in the tribe Gochnatieae (Compositae, Gochnatioideae) - María C. Tellería; Gisela Sancho; Vicky A. Funk; Iralys Ventosa; Nadia Roque (Plant Systematics and Evolution, 2013)

Testing a high-resolution satellite interpretation technique for crop area monitoring in developing countries - M. T. Marshall; G. J. Husak; J. Michaelsen; C. Funk; D. Pedreros; A. Adoum (International Journal of Remote Sensing, 2011)

Declining global per capita agricultural production and warming oceans threaten food security - Chris C. Funk; Molly E. Brown (Food Security, 2009)

Construction and characterization of a BAC-library for a key pollinator, the bumblebee Bombus terrestris L. - L. Wilfert; M. Muñoz Torres; C. Reber-Funk; R. Schmid-Hempel; J. Tomkins; J. Gadau; P. Schmid-Hempel (Insectes Sociaux, 2009)

The CRF1 receptor antagonist antalarmin attenuates yohimbine-induced increases in operant alcohol self-administration and reinstatement of alcohol seeking in rats - Peter W. Marinelli; Douglas Funk; Walter Juzytsch; Stephen Harding; Kenner C. Rice; Yavin Shaham; A. D. Lê (Psychopharmacology, 2007)

Molecular Phylogenetic Relationships Among Crested-tailed Mice (Genus Habromys) - Duke S. Rogers; Christopher C. Funk; Jacqueline R. Miller; Mark D. Engstrom (Journal of Mammalian Evolution, 2007)

PAQR Proteins: A Novel Membrane Receptor Family Defined by an Ancient7-Transmembrane Pass Motif - Y. Tom Tang; Tianhua Hu; Matthew Arterburn; Bryan Boyle; Jessica M. Bright; Peter C. Emtage; Walter D. Funk (Journal of Molecular Evolution, 2005)

Expression of functional hexahistidine-tagged ricinB in tobacco - Deborah G. Reed; Luis H. Nopo-Olazabal; Vanessa Funk; Bonnie J. Woffenden; Michael J. Reidy; Maureen C. Dolan; Carole L. Cramer; Fabricio Medina-Bolivar (Plant Cell Reports, 2005)

Behavioural structuring of relatedness in the spotted hyena ( Crocuta crocuta ) suggests direct fitness benefits of clan‐level cooperation - Russell C. Van Horn; Anne L. Engh; Kim T. Scribner; Stephan M. Funk; Kay E. Holekamp (Molecular Ecology, 2004)
Spotted hyenas ( Crocuta crocuta ) are gregarious carnivores that live in multigenerational social groups, called clans, containing one to several matrilines. Members of multiple matrilines within a clan cooperate during dangerous interactions with inter‐ and intraspecific competitors. The evolution of cooperation may be influenced by relatedness between individuals, which in turn is influenced by reproductive skew and mate choice, dispersal and territorial behaviours. Behavioural data exist for spotted hyenas, but corresponding data on patterns of relatedness are unavailable; this lack of data makes it difficult to assess the relative importance of selection pressures favouring cooperative behaviour within and among groups. Therefore we conducted a longitudinal analysis of relatedness within a single large clan of spotted hyenas, as well as a cross‐sectional analysis of relatedness among hyenas from multiple clans. Within a clan, patterns of relatedness reflected known pedigree relationships, and relatedness was higher within than among matrilines, even across generations. Although mean within‐matriline relatedness varied among matrilines, it did not decline with matriline rank. On average, clan members were not related closely, due to high levels of male‐mediated gene flow among clans, and relatedness declined very slightly across clan borders. Low mean relatedness within clans suggests that spotted hyenas cooperate with unrelated clan‐mates against close paternal kin in other clans. Our data also suggest that spotted hyenas must derive large net direct fitness benefits from group living and cooperation.

Sequence Analysis of DNA Fragments from the Genome of the Primary Endosymbiont of the Whitefly Bemisia tabaci - Linda Baumann; MyLo Ly Thao; C. Joel Funk; James C.K. Ng; Paul Baumann; Bryce W. Falk (Current Microbiology, 2004)

The relationship between flesh quality and numbers of Kudoa thyrsites plasmodia and spores in farmed Atlantic salmon, Salmo salar L. - J A Dawson‐Coates; J C Chase; V Funk; M H Booy; L R Haines; C L Falkenberg; D J Whitaker; R W Olafson; T W Pearson (Journal of Fish Diseases, 2003)
Atlantic salmon, Salmo salar L., were exposed to Kudoa thyrsites (Myxozoa, Myxosporea)‐containing sea water for 15 months, and then harvested and assessed for parasite burden and fillet quality. At harvest, parasites were enumerated in muscle samples from a variety of somatic and opercular sites, and mean counts were determined for each fish. After 6 days storage at 4 °C, fillet quality was determined by visual assessment and by analysis of muscle firmness using a texture analyzer. Fillet quality could best be predicted by determining mean parasite numbers and spore counts in all eight tissue samples (somatic and opercular) or in four fillet samples, as the counts from opercular samples alone showed greater variability and thus decreased reliability. The variability in both plasmodia and spore numbers between tissue samples taken from an individual fish indicated that the parasites were not uniformly distributed in the somatic musculature. Therefore, to best predict the probable level of fillet degradation caused by K. thyrsites infections, multiple samples must be taken from each fish. If this is performed, a mean plasmodia count of 0.3 mm −2 or a mean spore count of 4.0 × 10 5 g −1 of tissue are the levels where the probability of severe myoliquefaction becomes a significant risk.

Transformation of triploid bermudagrass (Cynodon dactylon x C. transvaalensis cv. TifEagle) by means of biolistic bombardment - G. Zhang; S. Lu; T. A. Chen; C. R. Funk; W. A. Meyer (Plant Cell Reports, 2003)

The city‐fox phenomenon: genetic consequences of a recent colonization of urban habitat - P. Wandeler; S. M. Funk; C. R. Largiadèr; S. Gloor; U. Breitenmoser (Molecular Ecology, 2003)
The red fox ( Vulpes vulpes ) is one of the best‐documented examples of a species that has successfully occupied cities and their suburbs during the last century. The city of Zurich (Switzerland) was colonized by red foxes 15 years ago and the number of recorded individuals has increased steadily since then. Here, we assessed the hypothesis that the fox population within the city of Zurich is isolated from adjacent rural fox populations against the alternative hypothesis that urban habitat acts as a constant sink for rural dispersers. We examined 11 microsatellite loci in 128 foxes from two urban areas, separated by the main river crossing the city, and three adjacent rural areas from the region of Zurich. Mean observed heterozygosity across individuals and the number of detected alleles were lower for foxes collected within the city as compared with their rural conspecifics. Genetic differentiation was significantly lower between rural than between rural and urban populations, and highest value of pairwise F ST was recorded between the two urban areas. Our results indicate that the two urban areas were independently founded by a small number of individuals from adjacent rural areas resulting in genetic drift and genetic differentiation between rural and urban fox populations. Population admixture and immigration analysis revealed that urban–rural gene flow was higher than expected from F ST statistics. In the five to seven generations since colonization, fox density has dramatically increased. Currently observed levels of migration between urban and rural populations will probably erode genetic differentiation over time.

Resistance of L132 lung cell clusters to glyoxal-induced apoptosis - C. Roehlecke; A.-K. Kuhnt; H. Fehrenbach; C. Werner; R.H.W. Funk; M. Kasper (Histochemistry and Cell Biology, 2000)

Schwefel-(Mitigal-)Vergiftung, medizinale - G. Funk; C. Bachem (Archives of Toxicology, 1930)